Air Power in War - Tedder, Lord (London Hodder and Stoughton, 1959)
Explores the career of Arthur Tedder, who was knighted and raised to the peerage for his contributions to the Allied victory in World War II, served in the British air force in World War I and played an important role in professionalizing and organizing British air forces between the two world wars.
Include Maps
The lees Knowles lectures by Marshal of the Royal Air force
Keywords: World War (1939-1945) -- Military Operations, Aerial -- Air Warfare